Unlawful Acts of Governance: Characteristics and Limits of Discretion - Muklis Al'anam; Lolita Fitriyana; Luthfillah Arrizqi Zainsyah (Universitas Negeri Surabaya, 2025)
Unlawful acts by the government are one of the fundamental issues in administrative law that are closely related to the principles of legality and the rule of law. Every government action must essentially be based on lawful authority, but in practice there is room for the necessary use of discretion to fill legal gaps, resolve emergency situations, or provide more effective public services. The characteristics of illegal actions by the government can be seen in actions taken without legal basis, exceeding authority, abusing authority, or contradicting the principles of good governance (AUPB). Meanwhile, discretion has strict normative limitations, namely that it must be in accordance with the purpose of the authority granted, not conflict with laws and regulations, and take into account proportionality, accountability, and the protection of citizens' rights. So, the study of illegal government actions and the limits of discretion is important to maintain the principle of legal certainty while maintaining a balance between the effectiveness of government administration and the protection of people's rights.